We cannot turn back time: a framework for restoring and repairing rivers in the Anthropocene - Greene, Rachel H.; Thoms, Martin C.; Parsons, Melissa (Frontiers in Environmental Science, 2023)
Restoration activities commonly aim to reverse the impacts of environmental degradation and return a system back to an original, ‘pre-disturbance’ condition. Is this realistic, achievable, or reflective of an unconscious bias in the Anthropocene; the current geological epoch where human disturbances dominate ecosystems? Billions of dollars are invested into river restoration globally each year but there is limited empirical data to evaluate river recovery to these activities. Current response models, typically based on concepts of equilibrium and stability, assume rivers return to pre-disturbance conditions by removing or ameliorating a disturbance or stressor. Conceptual frameworks are useful tools to order phenomena, material and understand patterns and processes in data limited situations. A framework for the recovery of rivers in the Anthropocene is presented. The framework includes components of resilience thinking, landscape ecology and river science. It is proposed that rivers in the Anthropocene have metamorphosised to a different basin of attraction (regime/state) that display alternative functions, structures, and interactions. Resilience thinking suggests that once a river moves beyond the Anthropocene tipping point, recovery back to its original state is not possible. If a river system cannot be returned to its original state, it must be repaired to something else. Using principles of landscape ecology for restoring structural and functional heterogeneity would enhance the capacity of Anthropocene rivers to withstand current and future disturbances. River science recognises the significance of physical heterogeneity at multiple scales, resulting differences in sensitivities to disturbance and associated recovery trajectories. All of which, should guide the selection of river restoration activity types at given locations within a river network.